1990
DOI: 10.1177/0095327x9001600206
|View full text |Cite
|
Sign up to set email alerts
|

Do Engineers Make Better Naval Officers?

Abstract: The hypothesis that engineering graduates are best suited for junior officer positions aboard increasingly sophisticated surface and submarine warships is tested empirically for a subset of 1,560 U.S. Naval Academy graduates from the classes 1976-80. Following the guidelines set by Admiral Rickover, policymakers presume the best preparation for leadership positions is provided by college majors that emphasize mathematics, sciences, and (especially) engineering. The results of the study, based on advanced multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Contrary to the findings regarding marital and dependency status above, Bowman (1990) found that marital status actually had a negative effect on nuclear officer retention.…”
Section: B Relevant Past Studiescontrasting
confidence: 99%
“…Contrary to the findings regarding marital and dependency status above, Bowman (1990) found that marital status actually had a negative effect on nuclear officer retention.…”
Section: B Relevant Past Studiescontrasting
confidence: 99%
“…The findings also support prior research that has found a positive relationship between academic achievement and earnings: those with better grades receive higher job performance ratings throughout their careers and are more likely to be promoted. Finally, the study finds little support for the hypothesis that a technical degree is necessary for success in this organization, despite the organization's stress on hiring those with technical majors (see Bowman 1990). …”
Section: Resultsmentioning
confidence: 82%
“…Studies of officer promotion (not nurse-specific) have shown a similar pattern, with accession source consistently identified as a significant influence on promotion [30][31][32].…”
Section: Discussionmentioning
confidence: 90%